Urban security management in the capitals of the former Yugoslav republics. (May 2013) - Meško, Gorazd; Tominc, Bernarda; Sotlar, Andrej
This article presents a study on urban security management in the capitals of the former Yugoslav republics (FYR): Ljubljana (Slovenia), Zagreb (Croatia), Sarajevo (Bosnia and Herzegovina), Belgrade (Serbia) and Skopje (FYR Macedonia). The article presents crime, natural disasters and other security threats in the region using semi-structured interviews with municipal security experts and officials as well as university researchers who deal with or manage security issues in the respective cities. The main findings show that collaboration between the various state and local organizations is necessary for the provision of safety and security in urban settings. Competencies, knowledge, skills and integrity are required for urban security managers and all partners in safety and security provision practice.